System of fundamentalization of professional training of future social workers on the basis of integration of innovative technologies - Rebukha, Liliya (Educological discourse, 2018)
Approaches to the definition of the fundamentalization of professional education, which are directed at improving traditional education,are actualized in the article. The direction of the fundamentalization of education, in which gained knowledge has a great professional potential (involvement of innovative social experience, leading achievements of humanity and its intellectual potential into the educational process, focus on the values of the future profession), is determined. The main components of the system of fundamentalization of the professional training of future social workers on the basis of the integration of innovative technologies are investigated, the theories and methodologies of education, the paradigms of education, goals, content, methods, forms and means of education, educational technologies and organizational systems are described. The content of educational disciplines is revealed in accordance with personally oriented and professionally oriented training strategies that are directed at self-development of the individual and taking into account the dynamism of the professional work of the social worker and the ever-increasing changes in social work. The criteria for selecting the content of university education are outlined and their division into internal, connected with the science, and external, as universal and socially recognized, professional values is made. It is concluded that the effectiveness of the system of fundamentalization of education is determined by the unification of fundamentalization, professionalization and integration of innovative technologies into a single, holistic process, which serve as the basis for the fundamentalization of the professional training of future specialists in the socio-humanitarian sphere.